PERANCANGAN MEJA TAMU SEBAGAI STORAGEMAINAN ANAK UNTUK COMPACT HOUSE DI SURABAYA - Karimah Abdul Bagi B.; Kresno Soelasmono; Wyna Herdiana (Perpustakaan Universitas Surabaya, 2018)
Abstract-The limitation of land and the high demand for land cause Surabaya’s people stay in narrow house. So there is a dual function on the room in that house, like living room which is also used as afamily room. So that, children often play in the living room and make the parents overwhelmed when the guest is coming. So that, this furniture is designed, that is coffee table as kids toys storage for compact house. This research done by in depth interview and observation method which is done on young family that live in small house in Surabaya as a case study this research. The designed product is guest table (coffee table) that also used as toys storage that raised the scandinavian design theme, where the design is focus on the function without rule out the aesthetic value of the product. This guest table (coffee table) is expected suitable with any livingroom, so this coffee table used neutral color, which is white and brown / cream. This coffee table have a shape that suitable for narrow house, where this product is not too takes place or space. Then with this product is expected can help answering the problems people that live in small house in Surabaya, where the limited space in house is no longer an obstacle to having a neat and beautiful house.